Four Quarters of Biographical Learning - Hanna Solarczyk-Szwec (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
The subject of the analysis is the discourse of biographical learning that is present in Polish andragogy. The key factors of the issue that are spread between biographical learning of the individual and community/society and awareness and unawareness of such process were singled out and among those elected fields (four quarters) further reflection was led. The aim of this action was reorganization of the discourse of biographical learning from the perspective of the chosen criteria which can set a basis for further research which could deepen the pedagogic value and meaning of lifelong learning.